(untitled) (Research, Society and Development, 2021)
This work aims to characterize the elemental concentrations of two banana types gold and silver. In both were analyze in the pulp and peel by X-Ray Fluorescence technique. The results showed that the elements in both types are more concentrated in the peel than in the pulp. In addition, it was also observed that the normalization of the peel and pulp concentrations for the elements K, Fe, Zn, Br, Rb, and Sr is higher in the silver banana compared to the gold banana. The results indicate that banana peels can be used to supplement nutritional deficiencies. The work also demonstrates the potential that X-Ray Fluorescence has in investigation of elemental composition of foods. As the technique has easy instrumentation and data interpretation, it can be implemented as a routine in the investigation of the elemental composition of foods. In addition, the technique has the advantage of carrying out in situ analyzes by portable instruments. These in situ investigations can even be applied to make quality control of bananas at the time of harvest.